1998
DOI: 10.1089/oli.1.1998.8.199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TNF-α Antisense Oligomers on Cytokine Production by Primary Murine Alveolar Macrophages

Abstract: Antisense oligomers can inhibit expression of a single gene in a sequence-specific manner. As a result, these sequences are being developed both as powerful experimental tools in the laboratory and as a novel class of therapeutic agents. In this study, we evaluated a panel of morpholino antisense (M-AS) oligomers for their ability to inhibit tumor necrosis factor-alpha (TNF-alpha) production by primary murine alveolar macrophages (AMs) and compared them with the more commonly used phosphorothioate oligonucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…25 One such modification in oligomer chemistry has led to the development of the phosphorodiamidate morpholino oligomers (PMO) by AVI BioPharma Inc. (Portland, OR), which are non-ionic antisense agents that inhibit gene expression by binding to RNA and sterically blocking processing or translation in an RNaseH-independent manner. [26][27][28] PMO antisense agents have revealed excellent safety profile and efficacy in multiple disease models [29][30][31][32][33][34][35][36][37] including cancer preclinical studies. [38][39][40][41][42][43][44] Recent studies in our laboratory have characterized in vivo PMO bioavailability in solid tumors and pharmacokinetics of the PMO agents in human clinical trials, revealing the potential of these agents in gene-specific targeting.…”
Section: Genomic-based Strategiesmentioning
confidence: 99%
“…25 One such modification in oligomer chemistry has led to the development of the phosphorodiamidate morpholino oligomers (PMO) by AVI BioPharma Inc. (Portland, OR), which are non-ionic antisense agents that inhibit gene expression by binding to RNA and sterically blocking processing or translation in an RNaseH-independent manner. [26][27][28] PMO antisense agents have revealed excellent safety profile and efficacy in multiple disease models [29][30][31][32][33][34][35][36][37] including cancer preclinical studies. [38][39][40][41][42][43][44] Recent studies in our laboratory have characterized in vivo PMO bioavailability in solid tumors and pharmacokinetics of the PMO agents in human clinical trials, revealing the potential of these agents in gene-specific targeting.…”
Section: Genomic-based Strategiesmentioning
confidence: 99%
“…When duplexed to RNA, they do not form a substrate for RNase H (72). Regions of eukaryotic mRNA sequence that are likely to be effective targets for PMO antisense agents can be predicted with relative ease and usually involve either pre-mRNA splice sites or the region comprising the 5Ј-untranslated region, the AUG translational start codon, and the first 20 or so bases of protein coding sequence (24,74,77). PMO treatment has resulted in efficacious and specific reduction of target protein levels in a number of tissue culture (40,43,45) and in vivo systems (6,31,58).…”
mentioning
confidence: 99%
“…This approach allowed the antisense molecules to be delivered as a renewable source under the control of the CMV promoter or the Visna LTR, rather than a single bolus, as employed in previous studies. [6][7][8][9][10] This study demonstrated by transient transfection that the 216 bp TNF␣ antisense was more effective than shorter (70 bp) or longer (750 bp) versions. Each of the antisense fragments constructed included the AUG transcription start site.…”
Section: Discussionmentioning
confidence: 83%
“…Although, many studies suggest that TNF␣ antisense molecules may be effective at inhibiting TNF␣ secretion, [6][7][8][9][10] controversy exists concerning the most effective TNF␣ antisense sequence. The 5Ј AUG transcription start site and sequences of the first exon flanking donor splice sites have recently been CMV promoter or the Visna LTR.…”
Section: Introductionmentioning
confidence: 99%